Drug Polymorphism: An Important Pre-formulation Tool in the Formulation Development of a Dosage Form - Singh, Prateek; Sharma, Shaweta; Sharma, Pramod K.; Alam, Aftab (Current Physical Chemistry, 2024)
Polymorphism permits solids to have two or multiple crystal structures with varying orientations or conformations, and polymorph drug dissolution and solubility vary. Polymorphism influences drug efficacy, bioavailability and toxicity. Various parameters can regulate polymorph crystallization, including supersaturation phase, temperature, stirring rate, solvent addition rate, seed crystal, additives and pH. To characterize and monitor polymorphs, various analytical approaches are available, including powder X-Ray diffraction / X-Ray diffraction (PXRD/XRD), also called as Gold Standard method, differential scanning calorimetry (DSC), Infrared spectroscopy (IR), and microscopical studies. To prevent polymorphic change during production, distribution, and storage, formulation with the most stable form in the marketed product is considered. In addition, by monitoring each phase of raw material processing, polymorphisms can be controlled during dosage form manufacturing. The objective of this review is to provide concise information on drug polymorphism, their characterization process, their effect on the stability of dosage forms, factors controlling polymorphism in the crystallization process, some case studies on polymorphs, control of polymorphism during the formulation of successful dosage forms and some of the regulatory considerations regarding polymorphs. Various databases like Pubmed/Medline, Google Scholar and Web of Science of all English language articles were searched, and relevant information was collected regarding the importance of polymorphism in formulation development. From a vast literature survey, it was found that polymorphism is a very important tool in a pre-formulation study that provides information about the fate of a drug molecule in its journey. From the present study, it was concluded that the polymorphism property of a drug should be taken into consideration at the pre-formulation stage since it is a very important tool for the formulation of a successful dosage form with stability and efficacy.
Keywords: solvates